Smartphone controlled hexapod for search rescue and payload delivery - J, Harikrishnan; Chandrika, Dega; Prasad, Aditi (International Journal of Engineering and Technology, 2018)
Rudra, the robotic hexapod has 6 independent actuators that are connected to specially designed semi-circular wheelbase for rugged motion. The robotic platform can conquer any terrain with ease and versatility. The advanced payload delivery system includes one 3 DOF arm along with a capacious block inside the body of the platform. The platform can devour any terrain including grass, gravel, mud, rocks, harsh terrain, asphalt, sand. The platform has a dynamic sensor system for real-time monitoring of its surroundings and a feedback to the end user.The entire platform is controlled by an android app.Â